Sediment dynamics on the outer-shelf of the Gulf of Lions during a storm: An approach based on acoustic glider and numerical modeling. (1st May 2022) - Gentil, Mathieu; Estournel, Claude; Durrieu de Madron, Xavier; Many, Gaël; Miles, Travis; Marsaleix, Patrick; Berné, Serge; Bourrin, François
Abstract: Describing and quantifying storm-induced sediment dynamics enables improved mapping of the fate of sediments over continental shelves, which is necessary to understand their role in the structure and dynamics of marine ecosystems, nutrient cycling, and dispersion of pollutants. Storms are episodic processes that can lead to massive sediment resuspension and transport on continental shelves. However, understanding sediment dynamics during storms remains a challenge, because these events are spatially under-sampled due to their intermittency and intensity. This paper quantifies processes that drive sediment dynamics and their spatiotemporal variability over the outer shelf of the Gulf of Lions (NW Mediterranean), during a 5-year return period storm, using an active acoustic glider combined with a hydrodynamic model (SYMPHONIE) and wave model (WAVEWATCH-III). The glider-ADCP (Acoustic Doppler Current Profiler) measurements proved invaluable validation of current vertical profiles of the hydrodynamic model during this episodic event. The combination of observations with numerical simulations suggest that sediment resuspension is an important process at depths greater than 90 m on the shelf. This appears to be primarily due to the wave forcing, which most likely accounts for some of the observed increase in suspended particulate matter in the water column. At the regional scale, an along shelf sediment transfer by successive jumps associated with onshore storms is suggested, from the main input (the Rhone River) to the output (the Cap de Creus) area of the Gulf of Lions' shelf. This study highlights the complementarity between numerical modeling and new observation instrument designed to spatially extend the measurement of current and turbidity to study sediment resuspension and transport during extreme events on continental shelves. Highlights: Active acoustic underwater glider monitors near-bed sediment processes during a 5-year return period storm. Waves are the primary driver of sediment resuspension for depths >90 m on the shelf. Numerical simulations suggest an along shelf transfer by successive jumps associated with onshore storms.